The Role of Technology in Shaping Education Leadership and Policy-Making For Abu Dhabi Private Schools - ALJABALI, RANA (2024)
The study 'The Role of Technology in Shaping Education Leadership and Policy-Making for Abu Dhabi Private School' reveals that with the increasing incorporation of digital tools in education, technology is revolutionizing the way leaders make well-versed decisions, involve stakeholders, and allocate resources. The study explores the way emerging technologies that include data analytics, e-learning tools, and digital communication platforms contribute to the development of education policies, policymakers, stakeholders, and nurture cooperation between stakeholders, policymakers, and educators. The research employed a mixed method that combines quantitative data from a survey session and qualitative viewpoints from in-depth interviews. It is obtained that the study sample involves 30 survey respondents along with four interview participants (Two educational leaders and two policymakers). The statistical tools that include SPSS were utilized to evaluate the quantitative data, and at the same time, thematic evaluation was implemented for the purpose of interpreting qualitative outcomes. The study also addressed noteworthy issues that include infrastructure limitations, the requirement for constant professional development and the digital divide to make sure policymakers and educators can completely leverage the potential of technology. At the same time, most of the respondents address the advantages of technology, and some express concerns based on the adequacy and accessibility of training offered to education leaders. The study concludes that technology noteworthily enhances decision-making, shareholder cooperation, and policy formulation; its accomplishment relies on identifying the associated issues. This dissertation contributes to understanding the changing role of technology in education and provides suggestions for its efficient incorporation.